2015
DOI: 10.3389/fmolb.2015.00016
|View full text |Cite
|
Sign up to set email alerts
|

Elements of the cellular metabolic structure

Abstract: A large number of studies have demonstrated the existence of metabolic covalent modifications in different molecular structures, which are able to store biochemical information that is not encoded by DNA. Some of these covalent mark patterns can be transmitted across generations (epigenetic changes). Recently, the emergence of Hopfield-like attractor dynamics has been observed in self-organized enzymatic networks, which have the capacity to store functional catalytic patterns that can be correctly recovered by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 358 publications
(376 reference statements)
2
49
0
Order By: Relevance
“…In summary, we present evidence that bovine macrophages can be “trained” to improve their lytic capacity, rather than just particle uptake, likely by epigenetic reprogramming [20, 21]. Our results are consistent with the concept of trained innate immunity recently proposed by Netea et al [1].…”
Section: Discussionsupporting
confidence: 90%
“…In summary, we present evidence that bovine macrophages can be “trained” to improve their lytic capacity, rather than just particle uptake, likely by epigenetic reprogramming [20, 21]. Our results are consistent with the concept of trained innate immunity recently proposed by Netea et al [1].…”
Section: Discussionsupporting
confidence: 90%
“…From a molecular point of view, the amoebas' locomotion is controlled by complex metabolic networks, which operate as non-linear systems with dynamics far from equilibrium 16 . These biochemical networks involve an intricate interplay of multiple components of the cell migration machinery, including the actin cytoskeleton, ion channels, transporters, regulatory proteins such as the Arp2/3 complex or the ADF/cofilin family proteins 17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence of the efficient self-regulatory activity of the metabolic networks, each amoeba seems to be endowed with the ability to orientate its movement toward specific goals in the external environment, thereby developing efficient foraging strategies even in conditions of sparse resources when there is limited or no information as to where food is located. A large number of experimental studies on individual cells have demonstrated that important systemic behaviors are supported by astounding metabolic properties 16 . For instance, the single cellamoeboid Physarumpolycephalum can find the minimum-length solution between two points in a maze 19 , forming an optimized network closely approaching the purposely designed Tokyo railway system 20 to resolve complex multiobjective foraging problems 21 , and to learn and recall past events 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Hopfield-like attractor dynamics have been observed in self-organized enzymatic networks which have the capacity to store functional catalytic patterns that can be correctly recovered by specific input stimuli 8 . In addition, evidences of functional memory which can be embedded in multiple stable molecular marks during epigenetic processes have been reported 9 . On the other hand, long-term correlations (mimicking short-term memory in neuronal systems) have also been analyzed in experimental calcium-activated chloride fluxes belonging to Xenopus laevis oocytes 10 .…”
Section: Conditioned Behavior Testmentioning
confidence: 99%